A Semiotic Analysis of Men’s and Women’s Representation in Royco and Masako Television Advertisements - Lasma Ida Mikha Theresia Rogate (Passage, 2017)
The present research which is entitled ‘A Semiotic Analysis of Men’s and Women’s Representation in Royco and Masako Television Advertisements’ aims to investigate how men and women are represented in Royco and Masako cooking products television advertisements. The present research also aims to reveal the meanings from the men’s and women’s representation. The present research employs a descriptive qualitative research design by conducting Kress and van Leeuwen’s (2006) The Grammar of Visual Design as investigative tool to conduct the research. The findings show that, in terms of physical appearances, the women are represented physically perfect; meanwhile, men are represented as physically ideal and healthy. In terms of occupations, the women are represented as professionals and at-home women; meanwhile, the men are represented as professionals and a chef. In terms of behaviors, the women are represented as ones who do women-related chores, such as cooking and taking care of children; meanwhile, the men are represented as ones who do non-traditional men-related chores, such as cooking, taking care of children, and gardening. Lastly, in terms of traits, the women are represented as strong, independent, warm, and affectionate; meanwhile, the men are represented as warm and affectionate. From the gender perspective, the findings reveal that the advertisements still conform to the Western traditional gender stereotypes of men and women, but it is less stereotyped due to a number of changes in portraying men and women.Keywords: Gender, stereotypes, the Grammar of Visual Design, representation, advertisements